Stambena arhitektura Beograda u 19. i početkom 20. veka = Residental architecture of Belgrad in the 19th and at the beginning of the 20th century - Roter Blagojević, Mirjana (Edicija Arhitektura u Srbiji ;, 2006)
Summary